A Comparison of the Effects of Phonation into a Positive Expiratory Pressure Device and Silicone Tube in Water on the Vocal Mechanism - Amarante Andrade, Pedro; Fric, Marek; Saccente-Kennedy, Brian; Hruska, Viktor (Elsevier, 2023)
Objectives: Positive expiratory pressure (PEP) devices have become an additional therapeutic approach for treating voice disorders. Similar to water resistance therapy (WRT), phonation in a PEP device introduces a secondary source of vibration within the vocal tract. This investigation aimed to compare the effects of phonation using a PEP device and silicone tube phonation (STP) commonly used in WRT on the vocal mechanism during phonation.